Aliansi Amerika Serikat dengan Jepang dalam Kebijakan Rebalancing di Kawasan Asia Pasifik 2011-2016 - Darma Kusuma, Agustinus Tri; Fasisaka, Idin; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT This research aimed to describe United States’ strategic alliance towards Japan. As China’s economic has rapidly grown, its military capability has also increased. United States saw this phenomenon as a threat and also an opportunity. United States then announced the rebalancing policy as a response to the rise of China. Rebalancing strategy provided United States to do certain approaches to Asia Pacific countries. Those approaches were aimed to United States’ partners and also China. Japan has been one of the United States’ strategic partners in Asia Pacific. The military relations between United States and Japan are based on the Japan-U.S. Security Treaty. Japan is also one of the United States’ partner that has issues involving China. United States’ military protection of Japan is essential regarding to Japan’s territorial dispute with China. United States implemented rebalancing policy to Japan through military and economy aspects. Keywords: Rebalancing strategy, United States, Japan, rise of China